Can perception be altered by change of reference? A test of the Social Reference Theory utilizing college students' judgments of attractiveness - Zhao, Sibo; Zhang, Jie (The Journal of general psychology, 2020)
Background: Social Reference Theory is relatively new in explaining and predicting social behaviors. Sophisticated empirical observations are needed to support and refine the theory. The theory proposes that (1) Any perception must be understood in the context of a reference; (2) without a reference, no perception exists; (3) changing the reference can change a person's perception; and (4) the reason different parties disagree on an issue is that they have difference references. Aim: This current study was to provide evidence for the Social Reference Theory with a focus on the third of the four propositions: changing the reference can change a person's perception. Method: A large sample of undergraduate students were randomly selected from a Chinese university and asked to participate in an online quasi-experimental survey to study the effect of changing a reference on subjects' evaluation of physical attractiveness. Subjects were asked to rate the attractiveness of an average-looking woman or man presented in the context of other photographs of either more attractive or less attractive women or men. Findings: These college students' perception of the targets' physical attractiveness were altered by a change of reference: an average image was rated high if the reference image was less attractive, and the same image was rated low if the reference was very attractive. Additionally, female respondents were more likely to be influenced by change of the reference than male respondents. Conclusions: This study provided evidence for the proposition that changing the reference can change a person's perception.